FDZ data description: Regional real estate price indices for Germany (RWI-GEO-REDX) - Version 12: 2008-11/2023 - Sandra Schaffner; Patrick Thiel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
The FDZ Ruhr at RWI provides price indices for apartments and houses (rentals and sales) in Germany starting in 2008. The price indices are based on the real estate dataset RWI-GEO-RED, which combines real estate listings from ImmoScout24. We perform three types of hedonic regressions to allow comparisons across time (annual or quarterly), across regions (labor market regions, counties, or municipalities), and in combination across time and regions. The data are publicly available and can be requested from the FDZ Ruhr website. A weakly anonymized version is also available for researchers on request. This data report is an updated version of previous reports and refers to RWI-GEO-REDX v12, which covers data until November 2023. – – Das FDZ Ruhr am RWI stellt Preisindizes für Wohnungen und Häuser (Vermietung und Verkauf) in Deutschland ab dem Jahr 2008 zur Verfügung. Die Preisindizes basieren auf dem Immobiliendatensatz RWI-GEO-RED, der Immobilienangebote von ImmoScout24 zusammenfasst. Wir führen drei Arten von hedonischen Regressionen durch, um Vergleiche über die Zeit (jährlich oder vierteljährlich), über Regionen (Arbeitsmarktregionen, Landkreise oder Gemeinden) und in Kombination über Zeit und Regionen zu ermöglichen. Die Daten sind öffentlich zugänglich und können auf der Website des FDZ Ruhr angefordert werden. Eine schwach anonymisierte Version ist für Forscher auf Anfrage ebenfalls erhältlich. Die vorliegende Datensatzbeschreibung ist eine aktualisierte Version früherer Berichte und bezieht sich auf RWI-GEO-REDX v12, die Daten bis November 2023 umfasst.
Keywords: 330